Rational matrix functions associated with the Nevanlinna-Pick problem in the class S [a, b] and orthogonal on a compact interval - Dyukarev, Yu. M.; Serikova, I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider the interpolation Nevanlinna-Pick problem with infinitely many interpolation nodes in the class S[a, b] and rational matrix functions associated with this problem and orthogonal on the segment [a, b]. We obtain a criterion of complete indeterminacy of the Nevanlinna-Pick problem in terms of orthogonal rational matrix functions.